Robert Motherwell and the New York School - Tatge, Catherine; Lacy, Susan; Cavander, Kenneth (PBS American masters series, 1991)
Explores the abstract expressionist movement and presents a portrait of artist Robert Motherwell. Features interview with Motherwell prior to his death in which he speaks about his work and the abstract expressionist movement. Archival footage and photographs of the artists of Greenwich Village where they lived, of the events which influenced their lives-WW II, the WPA, the Spanish Civil War- and interviews with art critics and art historians. Interwoven throughout the documentary is film of Motherwell showing us how he paints.